2014
DOI: 10.1080/15538362.2013.819748
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Resveratrol in Grapes Cultivated at High Altitude Valleys in Bolivia

Abstract: Trans-resveratrol, total antioxidant capacity (TAC), and total phenolic compounds were assessed in Bolivian grape cultivars collected at high altitude valleys. The TAC of the grapes ranged from 0.8 to 22 µmol Trolox equivalents/g dry matter determined by 2,2 -azino-bis(3-ethylbenzthiazoline-6-sulphonic acid), and from 0.6 to 10 determined by the ferric reduction antioxidant power. In the present study, we observed that under certain conditions trans-resveratrol levels in Bolivian grapes are 10-fold higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Grapes appear to synthetize the trans form and light causes trans / cis isomeration . Taquichiri et al . reported that trans ‐resveratrol concentration in grapes harvested from autochthonous and introduced Bolivian grapevine varieties was tenfold higher than the reported data from the literature.…”
Section: Minority and Autochthonous Varietiesmentioning
confidence: 93%
“…Grapes appear to synthetize the trans form and light causes trans / cis isomeration . Taquichiri et al . reported that trans ‐resveratrol concentration in grapes harvested from autochthonous and introduced Bolivian grapevine varieties was tenfold higher than the reported data from the literature.…”
Section: Minority and Autochthonous Varietiesmentioning
confidence: 93%
“…33 Additionally, other studies have found associations between the UV radiation and the increment of the phenolic content and thereby the antioxidant activity. 9,14 However, the phenolic content comparison among the red wine samples can be difficult to interpret since the polyphenol content is affected by several factors, such as grape varieties, vinification techniques, aging, weather conditions, soil characteristics, and solar UV radiation, thereby affecting their analytical determinability and, thus, their general profile. 34,35 This study provides new data about the chemical composition of wines from South America.…”
Section: Resultsmentioning
confidence: 99%
“…above the sea level are in accordance with other studies obtained from grapes growing at high altitude above the sea level, where higher values for TAC and resveratrol content were found. 14 In addition, it is important to note that non-varietal red wines showed the lowest values of TAC and had high saccharides content; furthermore, aging was found to be a noncontributor to the antioxidant values, since the oldest wines collected in this study were Uruguayan bottled in 2004 showing lower values for antioxidants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations